PENGEMBANGAN BUKU AJAR MATA PELAJARAN TATA HIDANG PAKET KEAHLIAN JASA BOGA SEKOLAH MENENGAH KEJURUAN - Yuli Astuti; Ahmad Sonhadji; Amat Nyoto (Graduate School of Universitas Negeri Malang, 2016)
Textbooks are the ingredients or the subject matter is arranged systematically used by students in the learning process. The purpose of this study was to develop teaching materials such as textbooks on the subjects of governance hidang class X SMK in Magetan consisting of 3 KD, namely, (1) The scope of food and beverage service, (2) Operating equipment food and beverage service, and (3) providing food and beverage service at the restaurant. The results show that the development of an overall assessment of the completeness of the presentation of the textbook of the development of criteria that are in